2021
DOI: 10.1021/acsaelm.0c01059
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Spin–Orbit Torque Efficiency in Pt/Co/Ru/Co/Pt Multilayers with Interlayer Exchange Couplings

Abstract: The magnetization manipulation by the current-induced spin–orbit torque opens a prospect for energy-efficient spintronic applications. Here, we investigate controllable spin–orbit torques (SOTs) realized by interlayer exchange coupling (IEC) in Pt/Co/Ru/Co/Pt stacks. The interlayer magnetization realignments originate from the competition between itinerant electron diffusion and current-induced spin current relaxation, and it is revealed that the long-ranged interlayer antiparallel orders exist with a Ru space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Also, the recent studies on Pt/Co/Ru/Co/Pt showed that the RKKY interlayer exchange coupling (IEC) could tailor the properties of the multilayers. 49 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the recent studies on Pt/Co/Ru/Co/Pt showed that the RKKY interlayer exchange coupling (IEC) could tailor the properties of the multilayers. 49 …”
Section: Introductionmentioning
confidence: 99%
“…Also, the recent studies on Pt/Co/Ru/Co/Pt showed that the RKKY interlayer exchange coupling (IEC) could tailor the properties of the multilayers. 49 In this paper, we present the detailed studies of the Co/Pt/ Co system with the use of the electrically detected FMR (ferromagnetic resonance), as well as low-frequency harmonic Hall voltage and static magnetotransport measurements. Here, the Pt layer plays a double role in the considered structure, first as a source of substantial spin currents and second as an essential element of the exchange ferromagnetic coupling mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we applied THz-TDS to studies of conduction in technologically-relevant metallic bilayer Ru/Co nanostructures of different thicknesses [14][15][16] , and of their individual constituent metals Ru and Co. Such structures find applications, among others, in spin-torque devices 17,18 , as well as in structures featuring magnetic skyrmions. [19][20][21] All the THz conductivity spectra measured in our work could be well described by the Drude model of free carrier conduction, and the conductivity of bilayers was analyzed based on an effective resistor network model.…”
mentioning
confidence: 99%